Home Quarantine or Home Isolation During the Covid-19 Pandemic as a Deprivation of Liberty under Polish Law - Sroka, Tomasz (Medicine, Law & Society, 2021)
Combating the COVID-19 pandemic requires that States should take many measures, which may also substantially interfere with the rights or freedoms of individuals. One commonly used mechanism to counter the spread of the SARS-CoV-2 virus is home quarantine or home isolation. Bearing in mind the guidelines arising from ECHR case-law, the article assesses whether home quarantine or home isolation applied under Polish law constitutes a deprivation of liberty. Taking into consideration the manner and conditions of these isolation measures and the possibility of using coercive measures, home quarantine or home isolation under Polish law constitutes deprivation of liberty within the meaning of Article 5(1)(e) of the ECHR. Then attention is drawn to selected consequences arising from this classification. In particular, it is emphasized that they cannot be imposed by a decision of the legislator, but only as a result of an act of law enforcement by sanitary authorities or courts.